Socio-technical mitigation effort to combat cyber propaganda: a systematic literature mapping - Maseri, Aimi Nadrah; Norman, Azah Anir; Eke, Christopher Ifeanyi; Ahmad, Atif; Abdul Molok, Nurul Nuha (Institute of Electrical and Electronics Engineers Inc., 2020)
This systematic mapping literature aims to identify current research and directions for future studies in terms of combating cyber propaganda in the social media, which is used by both human effort and technological approaches (socio-technical) for mitigation. Out of 5176 retrieved articles, only 98 of them were selected for primary studies; classified based on research artifacts, mitigation effort, and the social media platforms involved in the research. The search was conducted using selected databases and applying selection criteria set for this research. Through the analysis, important research trends were identifed based on human effort and technological approaches in mitigating and combating the cyber-propaganda issues. The authors also identifed various mitigation socio-technical approaches such as identication, detection, image recognition, prediction, truth discovery and comprehension of rumours flow. The study also highlights areas for further improvements, to complement the performances of existing techniques. Besides, the study provides a brief review of cyber propaganda detection using classication techniques. Hence, it has set forth applicable research focus on the areas dealing with the mitigation of risk borne by cyber propaganda in the social media.